Penentuan Indeks Kepadatan Pada Hutan Produksi PermanenDataran Rendah Di Kalimantan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Stand density plays an inipona lit role in regulating the rate of tree increment because it reflects the competition situation of nutrients. lights and space. The research was conducted using Reinekc's method (1933) in determining stand density index in natural forest. The lowland permanent production forest in Kalimantan was taken as the study area. The required data were number and total basal area 'primes with diameter larger than 10 cm in primary forest. These data were taken from first measurement of permanent plots in National Forest Inventory Project_ The natural logarithmic of number of (In N/ha) and diameter at average basal area (In did were drawn in scatter plot for interval class determination. Maximum values of every interval class was picked up to construct a regression equation. The slope of regression was then used to quantify the stand density index. The result showed that regression slope was found at -1.615 and this was very closed to Reineke's of -1.605. The stand density index for natural forest could be determined using the following formula: 25 -1,615 SI .}1hapdr= N /ha rt where SDI&writ =Stand Density Index for lowland puma nen production forest. Using the above formula. I he maximum stand density index found in the study area was 900.